Hakuna Nematoda: genetic and phenotypic diversity in African isolates of Caenorhabditis elegans and C. briggsae. - (:unkn) unknown (My University, 2008)
Caenorhabditis elegans and C. briggsae have many parallels in terms of morphology, life history and breeding system. Both species also share similar low levels of molecular diversity, although the global sampling of natural populations has been limited and geographically biased. In this study, we describe the first cultured isolates of C. elegans and C. briggsae from sub-Saharan Africa. We characterize these samples for patterns of nucleotide polymorphism and vulva precursor cell lineage, and conduct a series of hybrid crosses in C. briggsae to test for genetic incompatibilities. The distribution of genetic diversity confirms a lack of geographic structure to C. elegans sequences but shows genetic differentiation of C. briggsae into three distinct clades that may correspond to three latitudinal ranges. Despite low levels of molecular diversity, we find considerable variation in cell division frequency in African C. elegans for the P3.p vulva precursor cell, and in African C. briggsae for P4.p, a variation that was not previously observed in this species. Hybrid crosses did not reveal major incompatibilities between C. briggsae strains from Africa and elsewhere, and there was some evidence of inbreeding depression. These new African isolates suggest that important ecological factors may be shaping the patterns of diversity in C. briggsae, and that despite many similarities between C. elegans and C. briggsae, there may be more subtle differences in their natural histories than previously appreciated.
Keywords: African Research